Social entrepreneurship - the much-needed accelerator of the modern "green" economy - Stefan Chichevaliev; Tomislav Ortakovski (University American College Skopje, 2020)
Global environmental issues such including but not limited to air pollution, global warming, depletion of natural resources, waste disposal, and deforestation, have taken their toll on society. In North Macedonia, centralization of the population and its socio-economic status, complemented with low environmental awareness, have contributed to the increase of these issues and raised red flags for environmental calamity, reducing the quality of life of its citizens. The need for people-centered and evidence-based environmental policies and on-the-ground activities tackling these issues has been highlighted as a prerequisite for development of a healthier living environment, thus improving the quality of life. To tackle these environmental issues, practical and policy solutions are needed. As a nascent concept, social entrepreneurship has enormous potential to accelerate this transition toward sustainable development. This is a people-centered approach that includes undertaking business activities and adopting business models to achieve social change, in creating a better and healthier environment for all. This approach also provides a platform for connecting "green issues" with other social issues tackled within this sector. This research utilizes qualitative methodology combined with document analysis and case studies, to respond to the question "What can environmental organizations and social enterprises do to tackle environmental issues and contribute to development of a modern "green" economy?". The available evidence indicate that the lack of implementation of policies and laws, among other shortcomings, contribute to the affliction of the environment, diminishing the green economy. Existing traditional structures are not equipped to support organizations in their endeavors towards transformational change, and toward a paradigm shift of the conventional mindset as one of the preconditions for sustainable development. Facilitating the sustainability of future business activities that contribute to the green economy will be a new engine of growth and a net generator of decent jobs.
Keywords: 330; social entrepreneurship; social enterprises; green economy; green growth; sustainable development; policy; conducive environment